Mediasi Safety Knowledge Dan Safety Motivation Pada Pengaruh Safety Management Practices Terhadap Safety Performance Karyawan Bagian Produksi PT.Petrokimia Gresik - Novi Aditya Rosalita; Dwi Ratmawati; Tri Siwi Agustina (Universitas Airlangga, 2015)
Safety management practices not only improve working conditions but also positively influence employees’ attitudes and behaviours with regard to safety, thereby reducing accidents in workplace. This study measured employees’ perceptions on six safety management practices and self-reported safety knowledge, safety motivation, safety compliance and safety participation.The study conducting a survey using questionnaire among 69 pelaksana Produksi Pabrik III PT. Petrokimia Gresik. The reliability and validity of all the indicators were found acceptable. Data are analyzed using Partial Least Square (PLS) with SmartPLS version 2.0.The result is safety management practices have direct and significant influence to safety performance, safety management practices have indirect and significant influence to safety performance through safety knowledge, and safety management practices have indirect influence to safety performance through safety motivation.